Influence of Vaccination Characteristics on COVID-19 Vaccine Acceptance Among Working-Age People in Hong Kong, China: A Discrete Choice Experiment - Wang, Kailu; Wong, Eliza Lai-Yi; Cheung, Annie Wai-Ling; Yau, Peter Sen-Yung; Chung, Vincent Chi-Ho; Wong, Charlene Hoi-Lam; Dong, Dong; Wong, Samuel Yeung-Shan; Yeoh, Eng-Kiong (Frontiers in Public Health, 2021)
Background: Along with individual-level factors, vaccination-related characteristics are important in understanding COVID-19 vaccine hesitancy. This study aimed to determine the influence of these characteristics on vaccine acceptance to formulate promotion strategies after considering differences among respondents with different characteristics. Methods: An online discrete choice experiment was conducted among people aged 18 to 64 years in Hong Kong, China, from 26 to 28 February 2021. Respondents were asked to make choices regarding hypothetical vaccination programmes described by vaccination-related characteristics—the attributes derived from a prior individual interview. Subgroup analysis was performed to identify the differences in vaccination-related characteristics among respondents with different personal characteristics. Results: A total of 1773 respondents provided valid responses. The vaccine efficacy and brand were the most important factors affecting acceptance, followed by the exemption of quarantine for vaccinated travelers, safety, venue for vaccination, vaccine uptake of people in their lives, and recommendations by general physicians or government. Frequent exposure to vaccination information on social media has been associated with increasing vaccine refusal. Substantial preference heterogeneity for the attributes was found among people of different ages, incomes, chronic conditions, and previous acceptance of influenza vaccines. Conclusion: The findings provided evidence to formulate interventions to promote vaccine uptake, including the provision of vaccination at housing estate or workplaces, involvement of general physicians and interpersonal communication in vaccine promotion and information dissemination, and exemption of quarantine for vaccinated people. Moreover, social media is a significant information channel that cannot be neglected in the dissemination of official information.